2018
DOI: 10.3390/jof4020047
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment Responsive Modulations in the Fatty Acid Content, Cell Surface Hydrophobicity, and Adhesion of Candida albicans Cells

Abstract: Considering the significance in survival and virulence, we have made an attempt to understand modulations in the membrane and cell wall properties of Candida albicans hyphae induced by temperature (37 °C) and neutral pH and yeast form cells grown under low hydrostatic pressure (LHP). Our results suggest that cell surface hydrophobicity (CSH) and adhesion are dynamic properties determined largely by the microenvironment rather than morphological forms, citing the significance of variation in niche specific viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Adhesion, CSH and resistance to antifungals such as fluconazole may also be related, and increased CSH may lead to increased adherence and resistance to fluconazole in Candida spp [88]. However, contrary to the foregoing, some authors have not found a significant relationship between CSH and fluconazole resistance [89]. Adhesion of microorganisms to host mucosal surfaces is a vital prerequisite for successful microbial colonization and infection and so has an important role in the pathogenesis of Candida spp.…”
Section: Morphological Switchmentioning
confidence: 99%
See 1 more Smart Citation
“…Adhesion, CSH and resistance to antifungals such as fluconazole may also be related, and increased CSH may lead to increased adherence and resistance to fluconazole in Candida spp [88]. However, contrary to the foregoing, some authors have not found a significant relationship between CSH and fluconazole resistance [89]. Adhesion of microorganisms to host mucosal surfaces is a vital prerequisite for successful microbial colonization and infection and so has an important role in the pathogenesis of Candida spp.…”
Section: Morphological Switchmentioning
confidence: 99%
“…CSH and adhesion in Candida spp. are influenced by microbiome characteristics, considering that temperature of 37 °C, neutral pH and low hydrostatic pressure decrease hydrophobicity and adhesion [89].…”
Section: Morphological Switchmentioning
confidence: 99%
“…This may reflect differences in pH or glucose concentrations in the different environments, which exist in gradients from the center of a community of cells to the outside rim [135]. This conclusion could have important ramifications, because microenvironments play a role during infections by C. albicans, where intruders move from the site of infection to new tissues [206][207][208][209][210]. Microenvironments also play a major role in diseases like cancer [57,[211][212][213], including cancer cell invasion into new environments [214].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Signaling pathways (MAPK, cAMP-PKA, and HOG1) regulate morphophysiology of C. albicans cells in response to environmental cues [3,25]. Membrane properties are highly dynamic and reported to depend on morphological and growth forms of C. albicans [26]. Terpene-induced membrane integrity damage is reported to induce oxidative stress, enhance fluconazole uptake, and affect signaling pathways regulating hyphae induction, previously [14,16,17,19].…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 99%